Virtual Versus in-Person Physiotherapy Consultations Following Shoulder Pain (British Journal of Multidisciplinary and Advanced Studies, 2024)
The purpose of this evaluation was to analyse and compare the outcomes of virtual physiotherapy consultations versus in-person physiotherapy consultations following shoulder pain. The outcomes of 104 patients (49 virtual vs. 55 in-person) were reviewed. Shoulder function and pain scores were captured. Comparative analysis was performed using a two-tailed Student’s t-test. Total number of physiotherapy sessions and patient satisfaction scores were also recorded. Both modes of consultations showed significant improvements in shoulder function and pain scores when analyse separately, and when compared virtual physiotherapy consultations led to significant improvements in shoulder function and in-person physiotherapy consultations led to significant improvements in pain scores. Future research should focus on randomised controlled trials to directly compare virtual physiotherapy consultations and in-person physiotherapy consultations to confirm the findings of this evaluation.